2012
DOI: 10.1177/1528083712458304
|View full text |Cite
|
Sign up to set email alerts
|

Using slippage theory to analyze shear behavior of loop-formed fiber reinforced soil composites

Abstract: Since composite structures with soft-material matrix do not have adequate pullout resistance with flat-type reinforcements such as fibers, there are increasing cases where reinforcements with passive resistance are used in conjunction. So, loopformed polyethylene fibers were used to reinforce soil against shear loading. Afterward, shear behavior of both fiber and loop-formed fiber-reinforced soil composite samples was modeled by using ''force-equilibrium method'' and ''slippage theory'' of short fiber composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Randomly distributed fiber-reinforced soils have recently attracted increasing attention in geotechnical engineering for the second time [1,2]. Therefore, it is emphasized that short fiber composite soil is still a relatively new technique in geotechnical projects as a mimics of the past [3].…”
Section: Introductionmentioning
confidence: 99%
“…Randomly distributed fiber-reinforced soils have recently attracted increasing attention in geotechnical engineering for the second time [1,2]. Therefore, it is emphasized that short fiber composite soil is still a relatively new technique in geotechnical projects as a mimics of the past [3].…”
Section: Introductionmentioning
confidence: 99%
“…At this stage it can be concluded that pullout resistance of loop-formed fibers has two major components: (a) the friction between soil matrix and vertical elements of looped fiber (the fiber effect) and (b) shear resistance of soil matrix within the loop (the loop effect). Therefore, the total improvement in shear strength of soil composite (ÁS t ) can be written in the following format [5]…”
Section: Resultsmentioning
confidence: 99%
“…A hole (D = 4 mm) was entrenched on the mold, 15 mm above the horizon. More details can be found in the study of Hejazi et al [5]. On the base of optimum moisture content (OMC) (13.82%), the soil should be statically compacted in the mold to fill 30 mm of the mold.…”
Section: Determination Of Input Parameters For Micromechanical Analysismentioning
confidence: 99%
See 2 more Smart Citations